PERANAN BADAN USAHA MILIK DESA (BUMDES) PADA KESEJAHTERAAN MASYARAKAT PEDESAAN STUDI PADA BUMDES DI GUNUNG KIDUL, YOGYAKARTA - Maria Rosa Ratna Sri Anggraeni (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2016)
This research aims to explore the impact of the presence of village-owned enterprises(BUMD) on the welfare of the community. This research uses Community Based Researchin which the research was conducted in several stages, namely: in-depth interviews withparticipants who become the key actors in BUMDes, group discussions based on interestgroups that exist in the village, and Focus Group Discussion which the discussions wereconducted by various interested parties. It is conducted to confirm the findings in theprevious stage. The results of this study indicate that the existence of BUMDes do not bringa change in the economic and social fields. BUMDes existence do not bring significantbenefits to improving the welfare of citizens directly. The problems that arise related toBUMDes is people’s access to the water and to jobs in BUMDes.Keywords : Community Based Research, Village, Village-owned enterprises.